Decolourization of textile wastewater by using Lactobacillus immobilized on Bambusa heterostachya / Nur Hazirah Rosli - Rosli, Nur Hazirah (2016)
Colouring agents that are used in textile manufacturing processes have greatly contributed to environmental problems, particularly in the form of wastewater. The wastewater produced by this industry is highly coloured which increases the pollution level of the aquatic ecosystem, Various techniques of removing colour from textile wastewater being studied worldwide as concern mounts over the unavailability of a specific solution for treating the broad diversity of textile wastewater. There have been extensive researches into the treatment of textile wastewater by implementing modified biological approaches using bacteria. The enhancements of biological approaches using microbes with organic matrix in immobilization processes have been found to be useful. Thus, the application of a novel organic matrix, bamboo as a microbial matrix in an immobilization process is presented in this study. Bamboo’s physical characteristics have been studied as it has high porosity that qualifies it as an alternative microbial matrix. Lactobacillus delbrueckii was selected as the microbial agent. By using central composite design (CCD) to optimize the dye decolourization process with these significant parameters: agitation speed (10-150 rpm), dye concentration (10-100 mg/L) and Bambusa-Lactabacillus dosage (4—10 pieces); the experiments have been successfully conducted. The optimum condition for Bambusa as Lactobacillus matrix was found to be at pH of 7, 37°C and high concentration of M.R.S. broth under shaking condition. As for the decolourization process, this approach has successfully shown the ability m decolourize textile wastewater up to 75.43% with the correlation value of the model, R2 of 90.10% at the optimum condition of dye concentration, 50 mg/L, 7 pieces of Bambusa-Lactabacillus dosage under static condition These experiments have proven the effectiveness of implementing Lactobacillus immobilized on Bambusa heterastachya to decolourize textile wastewater.